Thermal and Fluid Flow Performance Analysis of Tubular Microchannel Heat Sinks with Inward Protrusions and Nanofluids - Ibrahim Ademola Fetuga; Olabode Thomas Olakoyejo; Antônio Marcos de Oliveira Siqueira; Joshua Kolawole Gbegudu; Ebenezer Aderibigbe Adeyemi (The Journal of Engineering and Exact Sciences)
In this work, the application of protrusions and nanofluids to improve the performance of tubular-microchannel heat sink (MCHS) is proposed and investigated computationally. The three-dimensional Navier-Stokes and energy equations were solved numerically using the finite volume method incorporated into the ANSYS (Fluent) software package. The effects of different types of nanofluid (Al2O3, CuO, ZnO in pure water), the volume fraction of the nanoparticles (0% to 4%)  and height of the protrusion ( 2um-6um) on microchannel heat sinks were investigated under the steady-state condition and Reynold numbers (400-2000) with constant heat flux of 9 x 106 W/m2. It was revealed that thermal performance improved as protrusion height increased. At Re=2 000  , for Al2O3 nanofluid (NAN) with a volume fraction ( of 4% and a protrusion height (H)  of  2um to 6um yielded a thermal performance value of 1.59, 1.68, 1.77, 1.86, and 1.96 times that of MCHS without the protrusion, respectively. In addition, at a volume fraction of 4%, protrusion height of 6um  and Reynolds number of 800, the Al2O3, CuO, and ZnO nanofluids yielded a thermal performance value of 1.79, 1.08, and 1.07 times that of pure water, respectively. Furthermore, at a Reynolds number of 400 and a volume fraction of 4%, the Al2O3–water nanofluid reduced the maximum temperature of the MCHS wall by 4% , whereas - and -nanofluids decreased the MCHS wall maximum temperature by 0.5% and 0.48% when compared to pure water, respectively. However, for all the cases of volume fraction (1% to 4%), there was an increase trend in the value of thermal performance for the Reynolds number range of 400 to 800 , and decrease with the Reynolds number range of 800 to 2 000.